PROTOPLAST SUSPENSION CULTURE OF LEAVES MESOPHYLOF Centella asiatica (L.) Urban AND QUALITATIVE ANALYSIS ASIATICOSIDE - Prihastanti, Erma; Soegihardjo, C. J.; Purbaningsih, Susiani (Indonesian Journal of Pharmacy, 2001)
Centella asiatica leaves has been used as diuretic, antihypertensi, anti leprae, skin infection, burning skin and celloid. Cells suspenson culture of mesophyll of Centella asiatica leaves were carried out in three steps: isolation, purification, and cell culture. The aim of this research is to investigate the influences of leaves position (age of leaves) and concentration of macerozyme R-10 for cells number and viability, and the influence of sucrose concentration for cells growth and biosynthesis of asiaticoside. Isolation and purification of mesophyll cell has been performed using factorial completely randomized design. The first factor was leaf position (age of leaves), and the second factor was concentration of macerozyme. Collected data were analysed using Anova and Duncan’s test at 0.0 – 2.5 – 5.0 and 7.5 per cent respectively. Asiaticoside produced by cell biomass were analyzed qualitatively using thin layer chro- matography. The result revealed that mesophyll cells could be used as explant for suspension culture. The highest biomass produced with highest viability were found in cells isolated from second leaves treated with 0.1% macerozyme (1.32 . 107 cells/ml). Addition of sucrose to suspension culture medium produced higher packed cells volume (pcv) percentage than no sucrose was added, (0% sucrose gave pcv 8.5%, 2.5% sucrose pcv 22%, sucrose 5% pcv 21.5%, and 7.5% sucrose pcv 15.75%). The asiaticoside production not only depended on sucrose, because without any sucrose was added, the asiaticoside was also available..Key Words: Cell suspension culture, mesophyll, Centella asiatica (L.) Urban, asiaticoside